Veno‐venous extracorporeal membrane oxygenation (ECMO) support during anaesthesia for oesophagectomy. (10th April 2013) - Schiff, J. H.; Köninger, J.; Teschner, J.; Henn‐Beilharz, A.; Rost, M.; Dubb, R.; Danassis, M.; Walther, A.
Summary The use of extracorporeal membrane oxygenation in adults has increased in popularity and importance for the support of patients with cardiac or pulmonary failure. Although it is now quite commonly used in the intensive care unit, its use has rarely been described as a means of support during anaesthesia and surgery. We report the case of a patient who required curative resection of the oesophagus following previous left pneumonectomy where veno‐venous extracorporeal membrane oxygenation was required both during surgery and for the first three days postoperatively. We describe the anaesthetic management of this patient who only had a single lung, review other alternatives and discuss why extracorporeal membrane oxygenation was particularly suited to this case. To the best of our knowledge, the anaesthetic literature to date does not contain a case report of this type.